2019
DOI: 10.1161/atvbaha.118.312301
|View full text |Cite
|
Sign up to set email alerts
|

Atheroprotective Flow Upregulates ITPR3 (Inositol 1,4,5-Trisphosphate Receptor 3) in Vascular Endothelium via KLF4 (Krüppel-Like Factor 4)-Mediated Histone Modifications

Abstract: Objective— The topographical distribution of atherosclerosis in vasculature underscores the importance of shear stress in regulating endothelium. With a systems approach integrating sequencing data, the current study aims to explore the link between shear stress-regulated master transcription factor and its regulation of endothelial cell (EC) function via epigenetic modifications. Approach and Results— H3K27ac (acetylation of histone 3 ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…IP3 receptors have also been implicated in playing an important role in atherosclerosis 28 , 29 . For instance, IP3R3 expression in human endothelial cells can be increased by atheroprotective pulsatile shear stress (PS) downstream of KLF4 48 . In support of this finding, we found IP3R1 mRNA and protein levels were significantly higher under a pulsatile shear stress of 12 dynes/cm 2 vs. oscillatory shear stress of 1 dynes/cm 2 using human aortic endothelial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…IP3 receptors have also been implicated in playing an important role in atherosclerosis 28 , 29 . For instance, IP3R3 expression in human endothelial cells can be increased by atheroprotective pulsatile shear stress (PS) downstream of KLF4 48 . In support of this finding, we found IP3R1 mRNA and protein levels were significantly higher under a pulsatile shear stress of 12 dynes/cm 2 vs. oscillatory shear stress of 1 dynes/cm 2 using human aortic endothelial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6c). He and colleagues recently demonstrated that KLF4 regulates Inositol 1,4,5-trisphosphate receptor type 3 (IPTR3) expression by increasing chromatin accessibility and H3K27 acetylation at the ITPR3 promotor region 42 . In addition, many microRNAs are shear stress-regulated 43 , perhaps most notably, miR-92a, that targets KLF2 and KLF4 under conditions of disturbed flow 44,45 .…”
Section: Fig 5: Klf4 Modulates Gene Expression Through Changes In Thementioning
confidence: 99%
“…The histone acetylation reader BRD4 and H3K27me3 writer EZH2 are powerful epigenetic regulators, as reported for proliferative diseases 11,14,26 and implicated for IH. While rapidly growing, epigenetic studies concerning IH are mostly reliant on cell cultures 21,22 . Here we report in vivo genome-wide epigenetic survey in arteries that undergo injury-induced IH.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenomic studies pertaining to IH have been limited and mostly confined to cell cultures 7,21,22 , which as oversimplified systems inevitably produce inaccurate information for interpreting in vivo pathogenic mechanisms 12,23 . Here we performed ChIPseq directly using rat carotid arteries that underwent angioplasty injury-induced IH.…”
Section: Introductionmentioning
confidence: 99%